Effectiveness Of Land And Building Tax Revenue Acceptance In The Regional Revenue Agency Of Bekasi City - Fadjar Tri Sakti; Engkus; Muhammad Farras Chaidar Lahay (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Abdusattorovich, B. A. (2024). Tax Control And Its Implementation In The Conditions Of The Shadow Economy. International Journal of Engineering Mathematics (Online), 6(1). Adams, C. F., & Adams, J. Q. (2024). Letters and addresses on Freemasonry. BoD–Books on Demand. Engkus, E., & Syamsir, A. (2021). Public organizational performance: Policy implementation in environmental management in Bandung City. Masyarakat, Kebudayaan Dan Politik, 34(4), 380. https://doi.org/10.20473/mkp.v34i42021.380-394 Gill, N., Drew, N., Rodrigues, M., Muhsen, H., Cano, G. M., Savage, M., ... & Funk, M. (2024). Bringing together the World Health Organization's QualityRights initiative and the World Psychiatric Association's programme on implementing alternatives to coercion in mental healthcare: a common goal for action. BJPsych Open, 10(1), e23. Huang, P., Lin, X., Liu, C., Fu, L., & Yu, L. (2024). A real-time automatic fire emergency evacuation route selection model based on decision-making processes of pedestrians. Safety science, 169, 106332. Kurniawan, A., Akbar, B., & Sinurat, M. (2024). Regional Tax Management Optimization Model to Realize Regional Financial Independence in Pekanbaru City, Riau Province. Influence: International Journal Of Science Review, 6(1), 18-32. Lubis. (2014). Perkembangan Teori Organisasi. Universitas Terbuka, Jakarta. Mahsun, M. (2013). Pengukuran Kinerja Sektor Publik. Yogyakarta: BPFE Yogyakarta. Mardiasmo. (2018). Akuntansi Sektor Publik. Yogyakarta: Andi. Mardiasmo. (2019). Perpajakan Edisi Revisi. Yogyakarta: Penerbit Andi. Maulana, I. T., Ambiyar, A., & Yulianti, R. (2024). Strategi Pengumpulan Data. Nurfadilah. (2022). Efektivitas Penerimaan Pajak Bumi dan Bangunan pada Badan Pendapatan Asli Daerah Kabupaten Gowa. Nalurita, A. S. (2024). The Market Traders' Perceptions of Land and Building Tax Collection (Case Study of Traders at Cicalengka Market). Jurnal Dialektika: Jurnal Ilmu Sosial, 22(2), 405-414. Pratiwi, I. (2014). Efektivitas Penerimaan Pajak Bumi Dan Bangunan Sektor Pedesaan dan Perkotaan di Kabupaten Bantul. Putri, R. A. (2021). Efektivitas Penerimaan Pajak Bumi Dan Bangunan (PBB) Pada Penerimaan Pendapatan Asli Daerah Di UPT Badan Pengelolaan Pajak Daerah Kecamatan Ilir Barat II Kota Palembang. Saputri, A. M., & Khoiriawati, N. (2021). Pengaruh pengetahuan pajak, sikap, dan kesadaran wajib pajak terhadap kepatuhan wajib pajak dalam membayar Pajak Bumi dan Bangunan. SOSEBI: Jurnal Penelitian Mahasiswa Ilmu Sosial Ekonomi dan Bisnis Islam, 1(1), 14-23. Saputri, R. D. A., & Nugraha, F. K. (2024). Analysis of the effect of tax rates and understanding of taxation on MSME taxpayer compliance in Lamongan Regency. Review: Journal of Multidisciplinary in Social Sciences, 1(03), 56-65. Siahaan, M. P. (2016). Pajak Daerah dan Retribusi Daerah. Jakarta: Rajawali Pers.  Sriyanti, G. A. A. K., Dewi, N. D. U., & Widanti, N. P. T. (2024). Effectiveness Of Digital Culture Services At Village Credit Institutions (Lpd Samsat) In Improving Motor Vehicle Tax Revenue At The Regional Revenue Agency Of Bali Province. Jurnal Dialektika: Jurnal Ilmu Sosial, 22(1), 123-131. Suandy, E. (2014). Hukum Pajak. Jakarta: Salemba Empat. Sugiyono. (2014). Metode Penelitian Pendidikan Pendekatan Kualitatif, Kuantitatif dan R&D. Bandung: Alfabeta. Supriyatin, T. (2021). Pengaruh Kualitas Sumberdaya Manusia dan Implementasi Kebijakan Dinas PUPR Terhadap Pembentukan Pola Ruang Di Kecamatan Bissappu Kabupaten Bantaeng Makassar. Makassar. Verweij, S., Haverhoek, V., Bergman, E., Westman, G., & Bloem, L. T. (2024). A natural language processing approach towards harmonized communication of uncertainties identified during the European medicine authorization process. Clinical Pharmacology & Therapeutics, 115(4), 871-880. Wanto, A. H. (2018). Strategi Pemerintah Kota Malang Dalam Meningkatkan Kualitas Pelayanan Publik Berbasis Konsep Smart City. JPSI (Journal of Public Sector Innovations), 2(1), 39. https://doi.org/10.26740/jpsi.v2n1.p39-43 Yang, C. (2024). Interval strategy-based regularization approach for force reconstruction with multi-source uncertainties. Computer Methods in Applied Mechanics and Engineering, 419, 116679. Yanti, K. E. M., Yuesti, A., & Bhegawati, D. A. S. (2021). Pengaruh NJOP, Sikap, Kesadaran Wajib Pajak, Pengetahuan Perpajakan, Dan SPPT Terhadap Kepatuhan Wajib Pajak Dalam Membayar Pajak Bumi Dan Bangunan Dengan Sanksi Pajak Sebagai Variabel Moderasi Di Kecamatan Denpasar Utara. Kumpulan Hasil Riset Mahasiswa Akuntansi (KHARISMA), 3(1). Yasin, M., Garancang, S., & Hamzah, A. A. (2024). Metode dan Instrumen Pengumpulan Data (Kualitatif dan Kuantitatif). Journal of International Multidisciplinary Research, 2(3), 161-173.